Resposta :
[tex]\boxed{\begin{array}{l}\sf m=\dfrac{2-[-2]}{5-[-1]}=\dfrac{2+2}{5+1}=\dfrac{4}{6}=\dfrac{2}{3}\\\sf y=2+\dfrac{2}{3}(x-5)\\\sf y=2+\dfrac{2}{3}x-\dfrac{10}{3}\\\sf y=-\dfrac{4}{3}+\dfrac{2}{3}x\end{array}}[/tex]
Resposta:
[tex]\textsf{Leia abaixo}[/tex]
Explicação passo-a-passo:
[tex]\mathsf{m = \dfrac{\Delta_Y}{\Delta_x} = \dfrac{y_B - y_A}{x_B - x_A} = \dfrac{2 - (-2)}{5 - (-1)} = \dfrac{2 + 2}{5 + 1} = \dfrac{4}{6} = \dfrac{2}{3}}[/tex]
[tex]\mathsf{y - y_0 = m(x - x_0)}[/tex]
[tex]\mathsf{y - 2 = \dfrac{2}{3}(x - 5)}[/tex]
[tex]\mathsf{3y - 6 = 2x - 10}[/tex]
[tex]\mathsf{3y = 2x - 4}[/tex]
[tex]\boxed{\boxed{\mathsf{y = \dfrac{2x}{3} - \dfrac{4}{3}}}}\leftarrow\textsf{equa{\c c}{\~a}o reduzida}[/tex]
[tex]\boxed{\boxed{\mathsf{2x - 3y - 4 = 0}}}\leftarrow\textsf{equa{\c c}{\~a}o geral}[/tex]